Endoscopic treatment of biliary complications in donors after living donor liver transplantation in a high volume transplant center - Erdoğan, Mehmet Ali; Çağın, Yasir Furkan; Atayan, Yahya; Bilgiç, Yılmaz; Yıldırım, Oğuzhan; Çalışkan, Ali Riza; Aladağ, Murat; Karıncaoğlu, Melih; Yılmaz, Sezai; Harputluoğlu, Muhsin Murat (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Although living donor liver transplantation (LDLT) has been accepted as a primary treatment for adults with end-stage liver disease, concerns about donor health have been emerged. As LDLT is technically complex, it creates perioperative morbidity and mortality risk in donors. Biliary complications such as stricture and leakage are seen most frequently in donors after liver transplantation. While some of these complications get treated with conservative approach, endoscopic, surgical, and percutaneous interventions may be required in some others. We aimed to present endoscopic retrograde cholangiography (ERC) results in donors who developed biliary complications after LDLT. Materials and Methods: Between June 2010 and January 2018, a total of 1521 donors (1291 right lobe grafts, 230 left lobe grafts) of patients who underwent LDLT, were retrospectively reviewed. 63 donors who underwent ERC due to biliary complication, were included in the study. Results: Biliary stricture was found in 1.6% (25/1521), biliary leakage in 2.1% (33/1521), and stricture and leakage together in 0.3% (5/1521) donors. Our endoscopic success rates in patients with biliary leakage, biliary stricture, and stricture and leakage were 85% (28/33), 92% (23/25), and 80% (4/5), respectively. Surgical treatment was performed on 12.6% (8/63) donors who failed ERC. Conclusion: We found that ERC is a successful treatment for post-LDLT donors who have biliary complications.